1989
DOI: 10.1001/jama.1989.03430010076034
|View full text |Cite
|
Sign up to set email alerts
|

Markers of HIV Infection Prior to IgG Antibody Seropositivity

Abstract: During a 1-year period of study at two plasma collection centers, 7 of 35,000 plasma donors seroconverted to the human immunodeficiency virus (HIV) and had stored plasma samples that predated or antedated the seroconversion period. From each donor, three to eight plasma samples that had been collected at 2- to 7-day intervals were tested for IgG and IgM antibodies to HIV with enzyme immunoassays, Western blot testing, and radioimmunoprecipitation assays. The presence of an HIV viremic phase was demonstrated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…These studies were based on analyses of stored blood specimens from seroconverting plasma donors or from subjects enrolled in high-risk cohort studies [1,2]. Similar results were subsequently reported for patients presenting with symptomatic primary HIV-1 infection (the acute HIV syndrome) [3].…”
Section: Projections Of Yield Prior To Implementationmentioning
confidence: 86%
See 1 more Smart Citation
“…These studies were based on analyses of stored blood specimens from seroconverting plasma donors or from subjects enrolled in high-risk cohort studies [1,2]. Similar results were subsequently reported for patients presenting with symptomatic primary HIV-1 infection (the acute HIV syndrome) [3].…”
Section: Projections Of Yield Prior To Implementationmentioning
confidence: 86%
“…Studies reporting detection of HIV-1 p24 antigen in serum prior to detection of antibody first appeared in 1986 [1][2][3]. These studies were based on analyses of stored blood specimens from seroconverting plasma donors or from subjects enrolled in high-risk cohort studies [1,2].…”
Section: Projections Of Yield Prior To Implementationmentioning
confidence: 99%
“…It was our initial hypothesis that because the produc tion of IgM antibodies is an early response to HIV-1 in fection [8], their determination by an IgM-specific immu noblot [9] could provide a possibility for early confirma tion of infection. In several screening studies of high-risk groups IgM antibodies to HIV-1 were detected in the early phase of infection, sometimes markedly before the ap pearance of IgG antibodies [10,11], The findings of other groups are not in agreement with these quoted studies [12]. They found that IgM antibody response overlaps the preence of HIV antigen during an approximately 10-day period preceding the development of IgG response.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, in some early infected EIA-negative patients, B cells, which make anti-HIV antibodies, can be expanded from peripheral blood in vitro [33]. Antibodies to HIV Nef and p17 proteins have are present before seroconversion in EIA [75,76]. Consequently, several studies indicate that immune responses occur early after infection and these do not necessarily involve induction of antibodies that react to linear epitopes of HIV proteins.…”
Section: Discussionmentioning
confidence: 99%